Knowing the Potential of Geometry as a Support Tool of the Curriculum Implementation with Competition Based in the Secondary School - Ibnu Ngatoillah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
The  purpose  this  article is  to  show the effect  of geometry as one of the  mathematical topies  in  the  secondary  school  as  a tool  in  supporting  the  curriculum  implementation with  competition  based.By using many  opinions  about  geometry,  we hope  that  teachers can do hardly  to  show the  potential  of geornetry.  It  means  to  know  what  kind  of aspects  that  must  be  to develop  by  teacl"rers  in  studying  geometry  in  secondary  schools in  general and joiner high  school in  particular, which  will  increase  the  pupils competition  such  that  give many  prifits.  This aim  can  be  achieved  by  processing,  controlling  and  studying  eachtopic  ir-r geometry  such  that  become  useful  thing  for  pupil.